Photocatalytic oxidative dehydrogenation of cyclohexane to cyclohexene over oxygen-deficient tungsten trioxide - Quan, Fengjiao; Zhan, Guangming; Liu, Xiufan; Zhou, Bing; Gu, Huayu; Yu, Linghao; Yang, Le; Jia, Falong; Liu, Xiao; Zhang, Lizhi (Applied catalysis. B, Environmental, 2021)
A mild photocatalytic process with the use of tungsten trioxide has been demonstrated as a promising strategy to boost oxidative dehydrogenation of C6H12. Through engineering the surface defects, oxygen-deficient WO3-x showed outstanding selectivity and stability to produce cyclohexene. [Display omitted] •Oxygen-deficient WO3-x was constructed for cyclohexane ODH to produce cyclohexene.•WO3-x showed photocatalytic ODH activity with high C6H10 selectivity and stability.•Oxygen vacancy introduction favored the adsorption of C6H12 over tungsten trioxide.•Low-coordinated W atom of WO3-x donated electrons to C6H12, weakening its CH bond.•C6H10 could easily desorb from WO3-x surface, contributing to the high selectivity. Oxidative dehydrogenation of cyclohexane (C6H12) to cyclohexene (C6H10) suffers from low selectivity due to its over-dehydrogenation and oxidation to other products like benzene or cyclohexanol. In this study, we report that oxygen-deficient tungsten trioxide (WO3-x) can realize photocatalytic oxidative dehydrogenation of C6H12 with high C6H10 selectivity (∼99 %) and stability. Experimental results and theoretical calculations revealed that the introduction of oxygen vacancy favored the adsorption of C6H12 over tungsten trioxide and the low-coordinated W atom of WO3-x would donate electrons to the C atom of C6H12, weakening its CH bond. During the photocatalysis, the photogenerated holes acted as oxidative species for the dehydrogenation of C6H12 along with the H2O formation through the combination with adjacent O atom in WO3-x. Meanwhile, the product C6H10 could easily desorb from the surface of WO3-x to avoid the over-dehydrogenation and oxidation, contributing to the high selectivity.